Exchange rate “Pass-through” on prices in Serbia in the post-crisis period - Ristanović, Vladimir; Tasić, Nikola (Industrija, 2018)
This paper follows a well-known pass-through effect of the foreign exchange rate at the inflation in the economy. Numerous econometric models show the existence of the influence of the foreign exchange rate on inflation. The aim of the paper is to evaluate how strong this effect is and whether the influence of the foreign exchange rate on price in Serbia after the collapse of the global economy is increasing/decreasing. The pass-through effect is assessed in the post-crisis period using the econometric model (ADL methodology). The results show that this effect exists, but that it is far below 1 and that it has been decreasing over time.